Estudio de la parrilla de programación de las radios comunitarias en la provincia de Loja y el servicio que generan a la comunidad urbana y rural, periodo noviembre 2017-marzo 2018. - Rueda Rodriguez, Nelvia Mercedes (2018)
The development of the present investigative work called: STUDY OF THE GRILL OF PROGRAMMING OF THE COMMUNITY RADIOS IN THE PROVINCE OF LOJA AND THE SERVICE THAT GENERATES THE URBAN AND RURAL COMMUNITY, PERIOD NOVEMBER 2017-MARCH 2018, arises from the need to be able to know which is the service that these radios generate through their programming to the urban and rural community, analyzing the quality of contents of the community broadcasting in the province of Loja, making a retrospective study and the evolution of the community radios of the province before and after the Communication Law to later identify the acceptance and influence of community radios in the Loja population. For the development of the research topic materials, methods, techniques and instruments were used, which allowed to obtain direct information directly, among the most used is the interview, which was made to each one of the members of the radios and to the representatives of the organisms that regulate them, based on the results, the conclusions and recommendations were built, it should be stressed that for all this research process it was necessary the participation of our respondents, the inhabitants of the cantons Saraguro and Puyango. With the results obtained it was verified the limitations and difficulties that these stations have in terms of their strengthening, development and creation of spaces specific to each sector, it was found that the participation of citizens in these radio programs is scarce, either by executing them or intervening in them, therefore, we proceeded to develop an alternative proposal aimed at solving this problem because as professionals we must link our university with the community.